95 Child Health Promotion Through Community Educational Sessions in an Urban Inuit Community: A Needs Assessment. (19th August 2020) - Hummel, Brian; Bierstone, Daniel; Jetty, Radha; Newhook, Dennis; Messam, Janice; Beadle, Trish; Sutherland, Stephanie
Abstract: Introduction/Background: Canadian Inuit children experience significant health disparities compared to their non-Inuit counterparts. Despite almost one-fifth of Canadian Inuit living in urban centres, few studies have explored their health needs. Current literature surveying Indigenous leaders identifies the need for improved access to child health and parenting knowledge. Community-based initiatives have been shown to improve Indigenous maternal and child health outcomes. Our study aimed to describe urban Inuit parents' perspectives on accessing child health knowledge to guide development of Inuit-specific health knowledge-sharing initiatives. Objectives: What are the barriers and facilitators faced by caregivers of Inuit children in an urban centre to accessing child health information? What child health topics would urban Inuit benefit from learning more about? What would be the best format and setting for the sharing of child health information with caregivers or Inuit children in an urban centre? Design/Methods: In conjunction with community partners, we conducted a qualitative needs assessment through focus groups at an urban-situated organization that provides cultural, educational, and social services to Inuit children and families. Participants were parents and caregivers of Inuit children. All focus groups were recorded, transcribed, and imported into NVivo software. Inductive coding was used to identify themes related to participants' sources of health knowledge, barriers and facilitators to accessing health knowledge, and health topics that participants hoped to learn more about. Results: Twenty-four individuals participated in four focus groups, of which twenty-one (88%) identified as Inuit. While participants represented a range of ages (19-40 years), most participants (42%) were 31-40 years old. The majority of participants (88%) identified as female. Participants had lived a median of 15 years in an urban setting (interquartile range 10-23). Seventeen participants (71%) cared for children aged 5 or younger. The main sources of health knowledge reported were Indigenous-focused services, online resources, telehealth and social networks (e.g. family and peers). The most notable barrier to accessing child health information was cultural differences (i.e. lifestyle and parenting practices). Discrimination and challenges with systems navigation also emerged as themes. Key health topics of interest included common childhood complaints (e.g. infections and immunizations), infant care, nutrition, parenting and development, mental health, and sexual education for adolescents. Preferred modes of child health information delivery were in-person sessions, pamphlets, and online videos with preferences for both health care providers and Inuit Elders as facilitators. Key access factors included Inuit language/translation, convenience of location, transportation, scheduling, and presence of food and childcare. Conclusion: Our results reveal important factors affecting access to child health knowledge among Inuit families in a large urban setting, as well as key child health topics of interest to this population. Informed by these findings and with help from our community partners, we are co-developing child health knowledge-sharing initiatives specific to the needs of the Inuit community in our region.